Infancies affected by state terrorism in Uruguay - Cassariego, Francesca (2023)
Through this article I propose to reflect on the memories of the childhoods affected during State terrorism, focusing mainly on Uruguay and from my personal expe- rience. When I was 3 years old, I was kidnapped as part of a Condor Plan operation, my brother and I remained missing for a couple of weeks. The case gained public notoriety and we were handed over to our grandparents; upon returning, as if I had a lump in my throat, nodules appeared on my vocal cords. The body inscribes the memory that the mind forgets. This is not just my story, there are many of us who had childhoods defragmented by State terrorism. Why history hardly talks about us? Why have we not found –in Uruguay– a place in the stories of memory? Why does our voice seem like my voice? that does not sound. These are some of the many questions that the Jacarandá collective asks. Culture of memory we become, and that personally I investigate. There are multiple effects experienced by those of us who spend our childhood during State terrorism and very diverse our experiences, therefore, this article is not exhaustive. In it, some experiences are outlined attempting to look at the childhoods that were the object of multiple violence during the Latin American dictatorships of the 60-80s. In turn, the analysis is approached from the perspective of affections, since this allows us to place emotions in the foreground (Pérez and Capdepón, 2022).